Metal pollution and floral abundance influence the diversity of flower visiting insects - Inge van Halder; Bastien Castagneyrol; Solenn Bernard; Florian Delerue (Arthropod-Plant Interactions, 2026)

The role of broadleaved hedgerows for biodiversity conservation in pine plantation landscape - Nattan Plat; Eric Allan; Severin Jouveau; Olivier Bonnard; Jean-Baptiste Rivoal; Jennifer Dudit; Tom Barlier; Yohan Charbonnier; Mathieu Sannier; Irene Garcia-Celada; Inge van Halder; Hervé Jactel (Biodiversity and Conservation, 2026)

Reduction of damage by the exotic invasive conifer seed bug Leptoglossus occidentalis in mixed pine-birch plantations: A case of biotic resistance - Ana Farinha; Bastien Castagneyrol; Inge van Halder; Manuela Branco; Céline Meredieu; Hervé Jactel (Forest Ecology and Management, 2024)

Decomposing drivers in avian insectivory: Large‐scale effects of climate, habitat and bird diversity - Laura Schillé; Elena Valdés‐Correcher; Frédéric Archaux; Flavius Bălăcenoiu; Mona Chor Bjørn; Michal Bogdziewicz; Thomas Boivin; Manuela Branco; Thomas Damestoy; Maarten de Groot; Jovan Dobrosavljević; Mihai‐Leonard Duduman; et al. (Journal of Biogeography, 2024)
Aim Climate is a major driver of large‐scale variability in biodiversity, as a likely result of more intense biotic interactions under warmer conditions. This idea fuelled decades of research on plant‐herbivore interactions, but much less is known about higher‐level trophic interactions. We addressed this research gap by characterizing both bird diversity and avian predation along a climatic gradient at the European scale. Location Europe. Taxon Insectivorous birds and pedunculate oaks. Methods We deployed plasticine caterpillars in 138 oak trees in 47 sites along a 19° latitudinal gradient in Europe to quantify bird insectivory through predation attempts. In addition, we used passive acoustic monitoring to (i) characterize the acoustic diversity of surrounding soundscapes; (ii) approximate bird abundance and activity through passive acoustic recordings; and (iii) infer both taxonomic and functional diversity of insectivorous birds from recordings. Results The functional diversity of insectivorous birds increased with warmer climates. Bird predation increased with forest cover and bird acoustic activity but decreased with mean annual temperature and functional richness of insectivorous birds. Contrary to our predictions, climatic clines in bird predation attempts were not directly mediated by changes in insectivorous bird diversity or acoustic activity, but climate and habitat still had independent effects on predation attempts. Main Conclusions Our study supports the hypothesis of an increase in the diversity of insectivorous birds towards warmer climates but refutes the idea that an increase in diversity would lead to more predation and advocates for better accounting for activity and abundance of insectivorous birds when studying the large‐scale variation in insect‐tree interactions.

Microbial biomarkers of tree water status for next‐generation biomonitoring of forest ecosystems - Marine C. Cambon; Marine Trillat; Isabelle Lesur‐Kupin; Régis Burlett; Emilie Chancerel; Erwan Guichoux; Lucie Piouceau; Bastien Castagneyrol; Grégoire Le Provost; Stéphane Robin; Yves Ritter; Inge Van Halder; et al. (Molecular Ecology, 2023)
Next‐generation biomonitoring proposes to combine machine‐learning algorithms with environmental DNA data to automate the monitoring of the Earth's major ecosystems. In the present study, we searched for molecular biomarkers of tree water status to develop next‐generation biomonitoring of forest ecosystems. Because phyllosphere microbial communities respond to both tree physiology and climate change, we investigated whether environmental DNA data from tree phyllosphere could be used as molecular biomarkers of tree water status in forest ecosystems. Using an amplicon sequencing approach, we analysed phyllosphere microbial communities of four tree species ( Quercus ilex , Quercus robur , Pinus pinaster and Betula pendula ) in a forest experiment composed of irrigated and non‐irrigated plots. We used these microbial community data to train a machine‐learning algorithm (Random Forest) to classify irrigated and non‐irrigated trees. The Random Forest algorithm detected tree water status from phyllosphere microbial community composition with more than 90% accuracy for oak species, and more than 75% for pine and birch. Phyllosphere fungal communities were more informative than phyllosphere bacterial communities in all tree species. Seven fungal amplicon sequence variants were identified as candidates for the development of molecular biomarkers of water status in oak trees. Altogether, our results show that microbial community data from tree phyllosphere provides information on tree water status in forest ecosystems and could be included in next‐generation biomonitoring programmes that would use in situ, real‐time sequencing of environmental DNA to help monitor the health of European temperate forest ecosystems.

Forests harbor more ticks than other habitats: A meta-analysis - Audrey Bourdin; Théo Dokhelar; Séverine Bord; Inge van Halder; Alex Stemmelen; Michael Scherer-Lorenzen; Hervé Jactel (Forest Ecology and Management, 2023)

Disentangling drivers of litter decomposition in a multi-continent network of tree diversity experiments - Ellen Desie; Juan Zuo; Kris Verheyen; Ika Djukic; Koenraad Van Meerbeek; Harald Auge; Nadia Barsoum; Christel Baum; Helge Bruelheide; Nico Eisenhauer; Heike Feldhaar; Olga Ferlian; et al. (Science of The Total Environment, 2023)

Changes in the foliar fungal community between oak leaf flushes along a latitudinal gradient in Europe - Álvaro Gaytán; Ahmed Abdelfattah; Maria Faticov; Xoaquín Moreira; Bastien Castagneyrol; Inge Van Halder; Pieter De Frenne; Camille Meeussen; Bart G. H. Timmermans; Jan P. J. G. Ten Hoopen; Pil U. Rasmussen; Nick Bos; et al. (Journal of Biogeography, 2022)
Aim Leaves support a large diversity of fungi, which are known to cause plant diseases, induce plant defences or influence leaf senescence and decomposition. To advance our understanding of how foliar fungal communities are structured and assembled, we assessed to what extent leaf flush and latitude can explain the within‐ and among‐tree variation in foliar fungal communities. Location A latitudinal gradient spanning c . 20 degrees in latitude in Europe. Taxa The foliar fungal community associated with a foundation tree species, the pedunculate oak Quercus robur . Methods We examined the main and interactive effects of leaf flush and latitude on the foliar fungal community by sampling 20 populations of the pedunculate oak Quercus robur across the tree's range. We used the ITS region as a target for characterization of fungal communities using DNA metabarcoding. Results Species composition, but not species richness, differed between leaf flushes. Across the latitudinal gradient, species richness was highest in the central part of the oak's distributional range, and foliar fungal community composition shifted along the latitudinal gradient. Among fungal guilds, the relative abundance of plant pathogens and mycoparasites was lower on the first leaf flush, and the relative abundance of plant pathogens and saprotrophs decreased with latitude. Conclusions Changes in community composition between leaf flushes and along the latitudinal gradient were mostly a result of species turnover. Overall, our findings demonstrate that leaf flush and latitude explain 5%–22% of the small‐ and large‐scale spatial variation in the foliar fungal community on a foundation tree within the temperate region. Using space‐for‐time substitution, we expect that foliar fungal community structure will change with climate warming, with an increase in the abundance of plant pathogens and mycoparasites at higher latitudes, with major consequences for plant health, species interactions and ecosystem dynamics.

Plant neighbour identity and invasive pathogen infection affect associational resistance to an invasive gall wasp - Pilar Fernandez-Conradi; Nicolas Borowiec; Xavier Capdevielle; Bastien Castagneyrol; Alberto Maltoni; Cécile Robin; Federico Selvi; Inge Van Halder; Fabrice Vétillard; Hervé Jactel (Biological Invasions, 2018)

Conserving butterflies in fragmented plantation forests: are edge and interior habitats equally important? - Inge van Halder; Luc Barbaro; Hervé Jactel (Journal of Insect Conservation, 2011)

Importance of semi-natural habitats for the conservation of butterfly communities in landscapes dominated by pine plantations - Inge van Halder; Luc Barbaro; Emmanuel Corcket; Hervé Jactel (Biodiversity and Conservation, 2008)